FEASIBILITY ASSESMENT PADA BANGUNAN GEDUNG NEGARA DI KABUPATEN TEGAL MELALUI PENDEKATAN LAIK FUNGSI BANGUNAN - Linda Puspasari; henny pratiwi adi; Hermin Poedjiastoeti (Pondasi, 2025)
Subdistrict office buildings, as public service infrastructure, play an important role in supporting government functions at the regional level. However, many office buildings are physically damaged or do not meet administrative requirements. This study aims to evaluate the suitability of district office buildings in Tegal Regency based on technical and administrative aspects in accordance with Ministry of Public Works and Housing Regulation No. 29/PRT/M/2006 and Law No. 28 of 2002 on Building Structures. The study was conducted on seven district offices: Bumijawa, Balapulang, Lebaksiu, Pagerbarang, Adiwerna, Talang, and Kramat. The methods used included a visual survey of structural, architectural, and utility elements with a weighting system (structure 40%, architecture 35%, utilities 25%) as well as an examination of administrative documents such as Land Certificates, KIB, IMB, and SLF. The research results showed that Talang Subdistrict had an average score of 1.41 and was categorized as Suitable. Bumijawa District (1.94), Balapulang District (1.98), and Lebaksiu District (2.01) are classified as Conditionally Feasible. Meanwhile, Pagerbarang District (2.74), Adiwerna District (2.63), and Kramat District (2.77) are categorized as Not Feasible. From an administrative perspective, none of the subdistricts have building permits (IMB) or site clearance certificates (SLF), resulting in an average administrative score of only 2 out of 4 points (50%). This study recommends gradual improvements, prioritizing technical rehabilitation budgets, and expediting the processing of legal documents to enhance the suitability of subdistrict office buildings